Family Microinsurance for Food, Medicines and Educational Support: A Product with a Differential Value in Case of Unemployment - Urrego Romero, John Edisson (Pontificia Universidad Javeriana, 2018)
Microinsurance (MS) is a product of protection to people in conditions of vulnerability that provides alternatives to mitigate the risk. The article wants to give an account of the innovation that a family MS has in the event of unemployment by covering food and providing support for education and medication for 6 months in populations vulnerable to unemployment in strata 1, 2 and 3 of the city of Bogota. The methodology used was a market study that allowed to establish the unfavorable conditions a level of formal and informal employability, food and social welfare in 3 neighborhoods of Bogotá to establish the coverages and conditions that should have the MS policy. This process of realization through an actuarial model that allowed it to calculate the TPRD (m) and TPRIT (m), Monthly Commercial Rates TCD (m) and TCIT (m) to calculate the Monthly Trade Premiums PCD) And PCIT (m) of the coverages for involuntary unemployment and temporary incapacity. According to the results obtained, the availability of the populations to acquire MS that are characterized by their low premium, food coverage with 20% in educational support and 20% of the medicines on one of the three alternatives of insured value that can be taken by the user to comply with the functionality of mitigating food risks and protecting the family and social development of each of these populations.